PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP HASIL BELAJAR FISIKA - La Isa; Halmuniati Halmuniati; Rahmawati Rahmawati; Zainuddin; La Ode Asmin (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to determine the effect of the generative learning model on physics learning outcomes in class XI IPA 1 SMAN 15 Konawe Selatan. This study uses an experimental method with a non-equivalent control design research design, in this design there is a pretest and posttest for the experimental and control classes. The sample was determined using a purposive sampling technique, namely class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The results showed that there was an effect of the generative learning model on physics learning outcomes after treatment in the experimental class and control class with tcount > ttable or 2,7 > 2,005. So it can be concluded that the effective generative learning model can improve student learning outcomes